2015
DOI: 10.1186/1472-6963-15-s1-s4
|View full text |Cite
|
Sign up to set email alerts
|

Peer-driven quality improvement among health workers and traditional birth attendants in Sierra Leone: linkages between providers’ organizational skills and relationships

Abstract: BackgroundSierra Leone has among the poorest maternal and child health indicators in the world and investments in public health have been predominately to increase demand for services, with fewer initiatives targeting supply side factors that influence health workers’ work environment. This paper uses data from the Quality Circles project in a rural district of Sierra Leone to achieve three objectives. First, we examine the effect of the intervention on organizational skills and relationships among coworkers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…These findings are consistent with studies showing that the use of QI methods and the QIC approach can empower health facility teams to identify and address process and management barriers to attaining high quality health services [19,20,23,27]. Contexts in which national guidelines and standards exist and quality challenges can be addressed at the facility level are optimal settings for QI interventions, which have been used successfully to address other quality challenges in Sierra Leone [28,29,30]. To our knowledge, this is the only study of QIC methodology to improve inpatient PITC coverage, but other PITC implementation projects report similar challenges, such as non-standardized workflows, suboptimal staffing and test kit shortages [10,11,31].…”
Section: Plos Onesupporting
confidence: 85%
See 1 more Smart Citation
“…These findings are consistent with studies showing that the use of QI methods and the QIC approach can empower health facility teams to identify and address process and management barriers to attaining high quality health services [19,20,23,27]. Contexts in which national guidelines and standards exist and quality challenges can be addressed at the facility level are optimal settings for QI interventions, which have been used successfully to address other quality challenges in Sierra Leone [28,29,30]. To our knowledge, this is the only study of QIC methodology to improve inpatient PITC coverage, but other PITC implementation projects report similar challenges, such as non-standardized workflows, suboptimal staffing and test kit shortages [10,11,31].…”
Section: Plos Onesupporting
confidence: 85%
“…The four QI learning sessions were well-attended, with an average of 50 participants attending each of the quarterly meetings. The initial training increased participant knowledge, as shown by improved performance on a multiple-choice test, from a median of 41% (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47) at the pretest to 73% (60-85) at the post-test (p < 0.0001). ICAP and MoHS provided twice-monthly supportive supervision, making a total of 188 site visits to the ten sites between October 2017 and August 2018.…”
Section: Resultsmentioning
confidence: 99%
“…It has been theorized that improved supervision and better relationships among the CHNs may have an impact on job satisfaction and motivation [ 7 , 8 ], as well as clinical knowledge and performance [ 9 ]. Some studies have found that collaborative skill-building can improve both performance and inter-personal relationships among health workers [ 10 , 11 ]. These questions are especially relevant to Ghanaian CHNs, given that these health workers live in environments of professional isolation and limited support.…”
Section: Introductionmentioning
confidence: 99%
“…Globally, about 295,000 maternal deaths were registered in 2017 and majority of these deaths occurred in low-income countries [1]. Sub-Saharan Africa accounts for 66% of maternal deaths globally (196 000) [1].…”
Section: Introductionmentioning
confidence: 99%
“…Globally, about 295,000 maternal deaths were registered in 2017 and majority of these deaths occurred in low-income countries [1]. Sub-Saharan Africa accounts for 66% of maternal deaths globally (196 000) [1]. Three sub-Sahara African countries; South Sudan, Chad and Sierra Leone have the highest maternal mortality ratios globally [1].…”
Section: Introductionmentioning
confidence: 99%